Literasi Muslim Dalam Memilih Sistem Perbankan di Indonesia Antara Bank Syariah atau Bank Konvensional: Muslim Literacy in Choosing a Banking System in Indonesia Between Islamic Banks or Conventional Banks - M Syahrul Syarifuddin; Dian Septi Purnamasari; Fajrin Intan Safitri (Journal of Islamic Economics and Philanthropy, 2023)
The current sharia financial and banking system, especially in Indonesia, is increasingly showing its rapid performance and development, especially in February 2021, which is the most important moment for the inauguration of the merger of three sharia state-owned banks. The merger of three state-owned Islamic banks is nothing but a form of government effort in providing facilities to the Indonesian Muslim community, increasing value for shareholders, increasing value for MSME players, the industrial sector, education, and other Islamic programs such as hajj savings, zakat waqf, Stiff Thought Muslims, is a challenge that will be faced by Indonesia in the process towards the 2030 call and becoming the center of world sharia finance. Is choosing an Islamic bank for the Indonesian Muslim community the best choice? It even becomes something that must be emulated by the Indonesian Muslim community, and if not, then there will be a view that "it is not said to be a true Muslim, if you still have funds and financing in conventional banks". The method used in this study uses qualitative comparative. If depositors, investors and debtors see the advantages that exist in banks based on the level of risk in facing the global financial crisis, then the choice of Islamic banks is the right choice. In general, the Islamic banking system is more stable than conventional banks. The reason is the Islamic banking system which does not recognize interest.Keywords: Banking System; Syariah banking; Asymmetric Information